Systematization in an curriculum reform - Perea R., José L. (2005)
The thematic one must like intention to approach the relation between currículo of theprofessional formation of the race of the Psychologist and the organizacional change, in a prospective of modernity of century XXI from the term of its first lustrum in the scope of the university superior education. Also it deals with the interrelation and consistency between new the basic conceptions or according to the purpose the professional field, in the fundamental stage of the curricular design, that will serve as support in the systematization of the management and evaluation of the curricular structure. Also, it is caused to that the consistency between the proposals of currículo for an integral formation or a technological formation, of the framed professional exercise in its normatividad, and of its pertinencia with the demands of the social reality exists, economic and political of the country.